Service Innovation Design Towards Ticketing System At Sungai Nibong Terminal - Hamim, Nur Syafawati; Majid, Ahmad Zuhairi Abdul (2014)
Service innovation design associated with the method of design for improvement and ease of service provided can immediately benefits to the user ofa service. At present, the development of new technological advances is growing exponentially and Malaysia as a developing country will not want to miss.This project is to study theexpress busticketing system at Sungai Nibong Express Bus Terminal, Penang. The project will find ways to provide a servicethat can satisfy usersby involving newelectronic device. Based on a survey it leads to designing a tool that facilitate users’ communication and be able to solve the problems faced by the users such as purchasing the tickets and or any information related to bus schedule.In addition, the purpose of this project is also to identify user needs and provide new experience to the users at Sungai Nibong bus terminal. Users are all from different age groups, cultures and backgrounds. The main goal of this project is to design a communication device to assist users in purchasing express bus tickets more easily. This design will enhance the user experience at Sungai Nibong bus terminal to buy tickets, provide comfort and facilitate user regardless locals or foreign users.